From Evidence to Policy Supporting Nepal’s Trade Integration Strategy : Designing Institutions to Promote Trade and Investment in Nepal - Gomez Mera, Laura (World Bank, Washington, DC, 2016)
As a small, landlocked economy, Nepal’s development prospects are closely tied to its ability to increase integration in the regional and global marketplace. Despite significant changes in Nepal’s trade sector over the past decade, the country’s export performance has remained poor, with exports growing at a much slower pace than imports. Nepal’s external vulnerability is deepened by its dependence on remittances to finance growing trade deficits.Achieving greater integration in the global economy and building a competitive export sector will require overcoming various economic and institutional challenges. This paper assesses the performance of these organizations in their role of promoting exports and investment. It has two main objectives. First, we describe the main export and investment promotion institutions in Nepal and examine their mandates, missions, and the services they offer.Second, we look at international best practices in export and investment promotion, to identify cost effective approaches appropriate for small developing countries. Based on this, we provide a number of recommendations for strengthening and improving the role of export and investment support organizations and initiatives in Nepal, as well as the level of coordination and cooperation among them. The report is organized as follows. In the next section, we briefly review the economic rationale for public intervention in the promotion of exports and investment and summarize the main findings of the literature regarding the most effective institutional designs and practices. We also discuss the arguments for and against a merger of the two activities within a single institution. Section three describes and assesses the institutional framework for export and investment promotion in Nepal. In Section four, we examine four case studies of “best practices” in the promotion of exports and export-oriented investment –Costa Rica, Jamaica, Colombia, and Latvia. We also discuss examples of successful promotion and development of the links between the tourism sector and exports, Mauritius, which offers some lessons for the case of Nepal. The final section contains the policy recommendations.